ALDOC and PGK1 coordinately induce glucose metabolism reprogramming and promote development of colorectal cancer - Liyong Huang; Yixin Tong; Xu Li; Wei Wang; Zhen Wang; Bingchen Chen; Jifu E.; Ruzhen Zhou; Hantao Wang; Jinghu He (Molecular Medicine)
Abstract Colorectal cancer (CRC) remains a significant health challenge globally, demanding a comprehensive understanding of its molecular underpinnings for effective management. In this study, we investigated the role of Aldolase C (ALDOC), a glycolytic enzyme, in CRC pathogenesis. Transcriptomic analysis of CRC tissues from The Cancer Genome Atlas (TCGA) revealed a substantial upregulation of ALDOC, correlating with adverse clinical outcomes. Immunohistochemical (IHC) staining of locally collected patient-derived tissues corroborated these findings, demonstrating elevated ALDOC expression in tumor tissues, particularly in advanced stages. Functional studies elucidated the regulatory role of ALDOC in CRC cell phenotypes. ALDOC knockdown significantly inhibited cell proliferation, induced apoptosis, arrested cell cycle progression, and suppressed cell migration in vitro. Moreover, in vivo studies using xenograft models confirmed that ALDOC knockdown attenuated tumor growth. Mechanistically, ALDOC was found to interact with hypoxia-inducible factor 1 alpha (HIF1A) and enhance its transcriptional activity on phosphoglycerate kinase 1 (PGK1), a key glycolytic enzyme. Dual-luciferase reporter assays and chromatin immunoprecipitation experiments validated the ALDOC-mediated transcriptional activation of PGK1. Further functional rescue experiments revealed a synergistic interplay between ALDOC and PGK1 in regulating CRC cell phenotypes. Additionally, ALDOC was implicated in promoting aerobic glycolysis in CRC cells, potentially through PGK1 regulation. Collectively, our findings unveil ALDOC as a critical regulator of CRC pathogenesis, offering insights into its potential as a therapeutic target and highlighting the ALDOC/PGK1 axis as a promising avenue for further investigation in CRC.